2000
DOI: 10.1590/s0103-84782000000300011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação histológica do processo de reparação da superfície articular de coelhos

Abstract: O processo de reparação da superfície articular foi avaliado microscopicamente em uma falha osteocondral produzida no sulco troclear esquerdo de 12 coelhos adultos. Observou-se preenchimento inicial com tecido de granulação, com diferenciação tecidual em cartilagem hialina e reposição parcial do osso subcondral excisado sete semanas após a cirurgia. Houve formação de fendas entre o tecido de reparação e o tecido ósseo adjacente, sempre em áreas onde não ocorreu remodelação óssea. Nos animais em que o fundo e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(31 reference statements)
2
3
0
2
Order By: Relevance
“…As cellular differentiation occurs, the repair tissue shows frequent fibrocartilage aspect and, at the deepest repair tissue region, new subchondral bone formation occurs. Such findings are in agreement with reports of Mitchel and Shepard (1976); Hurtig et al (1988);French et al (1989); Shamis et al (1989); Kim et al (1991), Shapiro et al (1993); Souza et al (1999); Souza et al (2000), who still mention that tissue architecture regeneration of articular surface is a rare event, occurring in a reduced number of osteochondral defects, a fact confirmed in this study, as there was no hyaline architecture restoration in any of the 48 animals used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As cellular differentiation occurs, the repair tissue shows frequent fibrocartilage aspect and, at the deepest repair tissue region, new subchondral bone formation occurs. Such findings are in agreement with reports of Mitchel and Shepard (1976); Hurtig et al (1988);French et al (1989); Shamis et al (1989); Kim et al (1991), Shapiro et al (1993); Souza et al (1999); Souza et al (2000), who still mention that tissue architecture regeneration of articular surface is a rare event, occurring in a reduced number of osteochondral defects, a fact confirmed in this study, as there was no hyaline architecture restoration in any of the 48 animals used.…”
Section: Discussionsupporting
confidence: 91%
“…The macroscopic findings of osteochondral defects from both groups at the end of T15 are in agreement with the report of Souza et al (2000), who noticed partial filling of defect by reddishpinkish repair tissue at 15 days after injury induction in the trochlear sulcus in rabbits. At 30 postoperative days (T30), partial filling by white-color tissue did not correspond to that found by Hurtig et al (1988), who reported that, when similar injuries were induced in the wrist of equines, there were few alterations at 30 postoperative days.…”
Section: Discussionsupporting
confidence: 91%
“…Chondrocytes isolated from non-articular cartilage contain larger amounts of lipid and glycogen inclusions due to the slower metabolism of this tissue [20,21]. In addition, studies have shown differences in the structure of ECM molecules isolated from cartilage obtained from anatomical sites that withstand compressive loads and those that do not [22].…”
Section: Introductionmentioning
confidence: 99%
“…O coelho é um animal amplamente utilizado em modelos para reparação da superfície articular (RIBEIRO, CAMANHO e TAKITA, 2004;Souza et al, 2000;O´Driscoll et al, 1988;Mow et al, 1991;Costa et al, 2001;Rudert et al, 2005;Hasegawa et al, 1999;Shahgaldi et al, 1998;Diduch et al, 2000;Mierish et al, 2002;Cohen et al, 2003;Frenkel et al, 2005;Uematsu et al, 2005;Shao et al, 2006;Witte et al, 2006;Suominen et al, 2006;Ohyabu et al, 2008). Porém, na literatura encontram-se diversos trabalhos com diferentes modelos animais como cães (Welsing et al, 2008), cabras (Custers et al, 2009), porcos (Chiang et al, 2005;Vassara et al, 2006), cavalos (Sams e Nixon, 1995), ovelhas (Erggelet et al, 2009), ratos (Kondo et al, 2005), carneiros (Kandel et al, 2006) e bugios (Malinin et al, 2006).…”
Section: Discussionunclassified
“…Na literatura consultada, constatou-se que tanto a região dos côndilos femorais (Mitchell e Sheperd, 1976;Inouye et al, 2002;Sakihama et al, 2006;RIBEIRO, CAMANHO e TAKITA, 2004;O´Driscoll et al, 1988;Mow et al, 1991;Messner e Gillquist, 1993;Diduch et al, 2000;Frenkel et al, 2005) como a região do sulco troclear Souza et al, 2000;Rudert et al, 2005;Hasegawa et al, 1999;Shahgaldi et al, 1998;Cohen et al, 2003;Uematsu et al, 2005;Witte et al, 2006;Suominen et al, 2006;Kandel et al, 2006) foram sede para estudos sobre reparo de cartilagem.…”
Section: Discussionunclassified